Mathematical Support of Decision Support System When Managing A Company - Mitsel A. A. Artur Aleksandrovich; Kozlov S. V. Sergei Vladimirovich; Kataev M. Yu. Mikhail Yurievich; Maslov A. V. Anatoliy Viktorovich (2016, 2016)
Title screen